The Impact of Artificial Intelligence on International Relations: Are Current Paradigms Still Relevant? - Kardumyan, Vrezh (YSU Journal of International Affairs, 2025)
This paper examines the increasing influence of Artificial Intelligence (AI) on International Relations (IR), with a particular emphasis on its transformative impact across the political, economic, and military-security spheres. It critically examines various scientific and theoretical discourses that define AI, situating these debates within key international relations (IR) paradigms—realism, liberalism, neoliberalism, and constructivism. The study explores how AI is reshaping the global balance of power, accelerating arms races, and enabling new forms of cooperation, while also introducing complex legal, political, and ethical challenges, especially in the context of international humanitarian law. Special attention is paid to the implications of AI for foreign policy decision-making processes and how technological advancements are reshaping established practices and norms. Furthermore, the paper contrasts anthropocentric and technocentric approaches, evaluating whether traditional IR theories and methodologies are sufficient to interpret, explain, and analyze the profound geopolitical and geo-economic transformations induced by AI. Ultimately, it assesses the capacity of IR scholarship to understand the realities of an increasingly AI-driven international system.